Effects of NPK Fertilizers, Household Waste Compost and Poultry Manure on Soil Fertility and Nutrient Uptake by Maize (Zea mays L.) - Hossain, N.; Kibria, M. G.; Osman, K. T. (International Journal of Bio-resource and Stress Management, 2023)
\6+ A field experiment was conducted to observe the comparative effects of fertilizers, household waste compost and poultry manure and their different combinations on soil fertility and nutrient uptake of maize (Zea mays L.). There were ten treatments, one control and nine fertilizer combinations. In three separate treatments, NPK, household compost and poultry manure were applied alone. In three treatments, NPK and compost were used in different proportions. In three other treatments, NPK and poultry manure were combined together. The results indicated that poultry manure alone or in different combination with inorganic fertilizer increased total N, available P, exchangeable K, Ca and Mg in soil after one month of treatment application; increased total N, exchangeable K and Ca after one month of sowing seeds of maize; and increased available P and exchangeable Ca at harvest over control. Increasing the proportion of NPK fertilizer with decreasing poultry manure decreased available P at harvest, exchangeable K and Mg at all the stages compared to poultry manure alone. Compost alone or in different combination with NPK fertilizer increased exchangeable K and Ca in soil at all the three stages. Nitrogen uptake by shoot, root and grain of maize varied significantly from 0.19 to 1.50, 0.01 to 0.19 and 0.07 to 1.43 g plant-1; P uptake from 0.04 to 0.42, 0.01 to 0.17 and 0.03 to 1.06 g plant-1, potassium from 0.14 to 3.04, 0.06 and 1.30, 0.04 and 1.80 g plant-1; Calcium uptake from 0.05 to 0.38, 0.01 to 0.18 and 0.00 to 0.07 g plant-1; and Mg uptake ranged from 0.03 to 0.34, 0.00 to 0.12 and 0.00 to 0.11 g plant-1, respectively. Uptake of nutrient was very low in control, low in full NPK, higher in compost and the highest in the poultry manure treatments.